LEVEL OF ERRORS, CHANGE IN DIAGNOSIS AND THEIR IMPACT ON MANAGEMENT IN CASES REFERRED FOR SECOND OPINION - Anwar, Madeeha; Asif, Muhammad; Ahmed, Rabia; Khadim, Muhammad Tahir; Jamal, Shahid; Mansur, Hamza (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of change in diagnosis and level of errors in cases referred to Armed Forces Institute of Pathology for second opinion and their impact on modifications of treatment and prognosis. Study Design: Cross sectional study. Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, form Mar to Oct 2017 Methodology: All the cases referred for review diagnosis were tested by applying panel of immunohistochemical markers and special stains on formalin fixed paraffin embedded tissue sections as decided on morphology. Level of errors were defined as level I error: minor discrepancy with no impact on management, level II: minor discrepancy with impact on management, level III: main category remains same but there was change/confirmation of specific diagnostic entity with an impact on management and level IV: gross changes in diagnosis with significant impact on management. Level IV was further subdivided into IV a: benign misdiagnosed as malignant, IV b: malignant misdiagnosed as benign and IV c: changes in tumor subtype. Results: A total of 100 cases, where review diagnosis was changed were included. Minor discrepancies (level I and level II) were observed in only 7% cases with little or no impact on the management. Most frequent discrepancy observed as Level III in 75% cases. Major discrepancy (Level IV errors) was noted in 18% cases. Conclusion: There were high discrepancy rates between previous diagnosis and review diagnosis. The higher use of extended panels of immunohistochemistry markers were the most likely explanations.